The role of α7-nicotinic acetylcholine receptor in a rat model of chronic nicotine-induced mechanical hypersensitivity. (19th January 2021) - Zhang, Yanping; Sevilla, Alec; Weller, Robert; Wang, Shuju; Gitlin, Melvin C.; Candiotti, Keith A.
Highlights: Chronic nicotine-induced mechanical hypersensitivity accompanied by decreased expression of α7-nAChR. CDP-choline, an α7-nAChR agonist, blocks nicotine-induced mechanical hypersensitivity. α7-nAChR agonist could be a potential therapeutic pain agent for smokers. The increase of neuro-immune factors is a potential factor leading to chronic pain in smokers. Abstract: Smokers have a higher incidence of chronic pain than non-smokers, but the neural mechanism is not yet fully understood. Nicotine is the main component of tobacco and acts as an agonist for nicotinic cholinergic receptors (nAChRs) in the nervous system. This study was approved by the IACUC of UM. The effects of chronic nicotine administration on mechanical sensitivity were studied using a rat model. The changes in the expression levels of the α7 isoform of nAChR (α7-nAChR), inflammatory cytokines TNFα and COX-2, as well as the density of neuro-immune cells (astrocytes and microglia) were measured concurrently. The results indicate that long-term nicotine administration induces hypersensitivity to mechanical stimuli, as demonstrated by a significant reduction in the pain perception threshold. In response to nicotine, the expression levels of α7-nAChR increased in the periaqueductal gray matter (PAG) and decreased in the spinal cord. Acute administration of the selective α7-nAChR agonist CDP-Choline reversed this hypersensitivity. Chronic nicotine administration led to an increase of microglial cells in the dorsal horn of the spinal cord and increased expression levels of the cytokines TNFα and COX-2. This study suggests that decreased α7-nAChR expression in the spinal cord, as a result of long-term exposure to nicotine, may be causatively linked to chronic pain. Simultaneously, the increase of neuro-immune factors in the spinal cord is also a potential factor leading to chronic pain.